PSYCHOLOGICAL PORTRAIT OF THE MAIN CHARACTER AKBAR IN ULUGBEK HAMDAM'S NOVEL "REBELLION AND HUMILITY" - Elvina Abdulkhakovna Azimova (Journals Park Publishing, 2024)
This article examines the psychological portrait of the main character Akbar in Ulugbek Hamdam's novel "Rebellion and Humility". An attempt has been made to analyze the spiritual world of the hero. The aim of the work is to reveal the psychological portrait of Akbar by studying his mental state.
Keywords: novel, hero, psychological portrait, psychological technique, symbol, image, psychological details.